Angular and frequency dependence of standing spin waves in FePt films - Jacobi, D. M. (2012)
We present a detailed analysis of the dynamic response of the magnetization in as-made FePt thin films, particularly studying the angular dependence of standing spin waves that can be observed when the external field is applied close to the film normal. We have found that the field separation between the uniform and the first excited mode depends strongly on angle and microwave frequency. To explain the observed behavior we have adopted the surface inhomogeneity model in the circular precession approximation. Using this model the experimental data could be very well fitted assuming that spins are not totally pinned at the surfaces by introducing a finite surface anisotropy. The experimental angular behavior of the resonance field at three different frequencies could be fitted with a single set of parameters indicating that the reported changes in the surface anisotropy as a function of film thickness are intrinsic to the samples.